Marketing Exposure Recall is Associated With Past 30-Day Single, Dual, Polytobacco Use Among US Adolescents. (14th August 2018) - Mantey, Dale S; Creamer, MeLisa R; Pasch, Keryn E; Perry, Cheryl L
Abstract: Introduction: This study assesses the relationship between tobacco/e-cigarette marketing exposure and single, dual, and polytobacco product use, among adolescents. Given the increased use of noncigarette tobacco products (eg, cigars, e-cigarettes, hookah) among youth, it is imperative to understand if marketing exposure is associated with dual and polytobacco product use. Methods: Data were obtained from the 2014 National Youth Tobacco Survey and weighted to be representative of US middle and high school students. Multivariable multinomial logistic regression models were used to assess the relationships between product marketing (via internet, print, retail, and TV/movies) and past 30-day single, dual, and poly (three or more) tobacco product use. Three analyses were conducted using different categories as referent groups to allow for comprehensive examination of the relationships between all groups. Results: Marketing exposure was significantly correlated with a greater risk of single, dual, and polytobacco product use relative to nonusers. Relative to single product users, product marketing exposure was significantly correlated with a greater relative risk of dual and polytobacco use. There was no statistical difference in the association of marketing exposure between dual and polytobacco use, in any model. Conclusion: A positive relationship between tobacco product marketing exposure and number of tobacco products used was observed. The magnitude of the relationship grew from single product to dual/poly use. Restrictions of marketing of all tobacco products, similar to cigarettes, particularly in the retail setting, should be considered. Implications: This study has two primary public health implications. First, self-reported exposure to tobacco/e-cigarette marketing is widespread among adolescents of all tobacco product categories. Second, this widespread exposure to tobacco/e-cigarette marketing appears to not only be correlated with use of a single tobacco product (eg, cigarettes, e-cigarettes), but also multiple tobacco products. While longitudinal studies are needed to further investigate the relationships observed in this study, findings justify further study given the known relationship between tobacco marketing exposure and subsequent cigarette use.